2021
DOI: 10.1111/rec.13556
|View full text |Cite
|
Sign up to set email alerts
|

Corridors in heavily fragmented landscapes: reconnecting populations of critically endangered brown spider monkeys (Ateles hybridus) and sympatric terrestrial vertebrates in the lowland rainforests of Central Colombia

Abstract: In tropical ecosystems, habitat degradation and fragmentation are some of the most important drivers of biodiversity loss. In Colombia, the Magdalena River basin is home to a megadiverse wildlife community, which has been historically exposed to pervasive habitat loss and fragmentation. Within a long‐term project on the conservation of critically endangered brown spider monkeys (Ateles hybridus), we signed conservation agreements with local landowners to protect the remaining forests and reconnect them through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The urgent need for restoration in the Andes and Caribbean has been pointed out on multiple occasions because these regions are the most transformed in the country despite being home to a great diversity of ecosystems and species, including the critically endangered tropical dry forest biome (Aldana-Domínguez et al, 2017; Etter, Andrade, Saavedra, et al, 2017; Etter et al, 2020a; Etter & van Wyngaarden, 2000). Restoration in these regions could lead to significant conservation benefits for birds, as it helps to mitigate the impacts of climate change and to connect remnant habitat fragments (Masson-Delmotte et al, 2018; Montealegre-Talero et al, 2017; Torres et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The urgent need for restoration in the Andes and Caribbean has been pointed out on multiple occasions because these regions are the most transformed in the country despite being home to a great diversity of ecosystems and species, including the critically endangered tropical dry forest biome (Aldana-Domínguez et al, 2017; Etter, Andrade, Saavedra, et al, 2017; Etter et al, 2020a; Etter & van Wyngaarden, 2000). Restoration in these regions could lead to significant conservation benefits for birds, as it helps to mitigate the impacts of climate change and to connect remnant habitat fragments (Masson-Delmotte et al, 2018; Montealegre-Talero et al, 2017; Torres et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A long‐term field experiment on the restoration of rainforest vegetation in the same region has not only identified the native tree species that could be planted to establish corridors, but has also shown that the rainforest can be successfully reestablished within a period of just two decades (Mudappa & Shankar Raman, 2007; Osuri et al., 2017, 2019). The corridors established for brown spider monkeys ( Ateles hybridus ) were used by 21 of 32 vertebrate species of the region in a highly fragmented landscape in central Colombia, and the 5‐year‐old corridors had no structural difference with forest fragments (Torres et al., 2021). The natural canopy bridge established over a railway line for the movement of gibbons ( Hoolock hoolock ) provided the facility for six other sympatric primates in the Holongapar Gibbon Sanctuary in India (Chetry et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The corridors established for brown spider monkeys (Ateles hybridus) were used by 21 of 32 vertebrate species of the region in a highly fragmented landscape in central Colombia, and the 5-year-old corridors had no structural difference with forest fragments(Torres et al, 2021). The natural canopy bridge established over a railwayF I G U R E 7 Modeled potential distribution of mixed-species groups of Nilgiri langur and Hanuman langur.…”
mentioning
confidence: 99%
“…This has left 25% of its ecosystems critically endangered (Etter et al., 2020). Restoration activities in Colombia are frequently underscored as an important strategy for reversing Colombia's biodiversity declines (Calle & Holl, 2019; Ocampo‐Peñuela et al., 2022; Torres et al., 2022). Our restoration assessment takes into account potential conflicts with agriculture production, the capacity for natural forest regeneration, and aligns with Colombia's national targets around forest regeneration.…”
Section: Introductionmentioning
confidence: 99%